Identification of targeted epitopes of yellow fever virus based on homology with other species of flavivirus - Lima, Michelle Pacheco de (2017)
Fundação Oswaldo Cruz. Centro de Desenvolvimento Tecnológico em Saúde. Laboratório de bioquímica de proteínas e peptídeos. Rio de Janeiro, RJ.